2013
DOI: 10.5210/fm.v18i6.4370
|View full text |Cite
|
Sign up to set email alerts
|

Economics of scholarly communication in transition

Abstract: Academic library budgets are the primary source of revenue for scholarly journal publishing. There is more than enough money in the budgets of academic libraries to fund a fully open access scholarly journal publishing system. Seeking efficiencies, such as a reasonable average cost per article, will be key to a successful transition. This article presents macro level economic data and analysis illustrating the key factors and potential for cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…The 2014 global average APC of $964 USD reported by Morrison et al (2013) is very similar to the 2011 global average of $906 USD reported by Solomon & Björk (2012 Other research targets include both fully OA and hybrid journals. recently released a major study of 7,629 APC payment records from four European APC payment databases and 14,356 APC payments from five large North American based universities committed to APCs through the Pay it Forward project.…”
Section: Abstract Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The 2014 global average APC of $964 USD reported by Morrison et al (2013) is very similar to the 2011 global average of $906 USD reported by Solomon & Björk (2012 Other research targets include both fully OA and hybrid journals. recently released a major study of 7,629 APC payment records from four European APC payment databases and 14,356 APC payments from five large North American based universities committed to APCs through the Pay it Forward project.…”
Section: Abstract Introductionsupporting
confidence: 63%
“…According to Morrison (2013), the current global spend by academic libraries is more than sufficient to fund a fully Open Access scholarly publishing system. There is potential to transition the system and achieve significant cost savings at the same time.…”
mentioning
confidence: 99%
“…Morrison [11] argues that behind the variety of models for economic support for open access journals, the basic underlying strategy involves shifting from demand-side to supply-side economics. Instead of charging readers and librarians for subscriptions, licenses, or purchase of scholarly works, open access business models involve supporting the production costs.…”
Section: Background and Rationalementioning
confidence: 99%
“…Entre ellos, la adaptación a los cambios asociados al desarrollo de la filosofía del acceso abierto (Crow y Goldstein, 2003;Chi Chang, 2006;Lamberti y Solaro, 2011;Dai y otros, 2014;Das, 2015;Schimmer y otros, 2015); las discusiones y propuestas en torno a la viabilidad financiera de las revistas (Björk y Hedlund, 2009;Crow, 2009;Houghton y otros, 2009;Morrison, 2013); los debates en torno a los índices de calidad o de impacto (Bordons y otros, 2002;Björk y Solomon, 2012;Riera y Aibar, 2013); la preocupación por la visibilidad y el posicionamiento internacional de las revistas científicas (Buela Casal, 2001;Abadal y Rius Alcaraz, 2008;Aréchaga, 2009;Rodríguez-Yunta, 2015) y, más recientemente, el impacto de los requerimientos de la ley y las normativas universitarias que obligan a poner a disposición pública los resultados de la investigación financiada con fondos públicos y otros desafíos políticos de la ciencia abierta (Friend, 2011;Abadal y otros, 2013; Rodríguez-Yunta y Giménez-Toledo, 2013; Alonso y Echevarría, 2014; García Arístegui y Rendueles, 2014).…”
Section: Introductionunclassified